Quality of life of parents and siblings of children with cochlear implants - Umat, Cila (J Otol, 2019)
OBJECTIVES: This study examined the quality of life (QoL) of the parents and siblings of hearing-impaired children with cochlear implants (CIs). DESIGN: This is a cross-sectional, questionnaire-based study. The questionnaire consists of three sub-domains - interaction, emotional well-being and support for the hearing-impaired child and the overall QoL -- and two open-ended questions for participants to provide comments and suggestions to enhance their family's QoL. A total of 63 questionnaires were e-mailed or mailed to families who met the inclusion criteria. SETTING: The study was conducted under the Center for Rehabilitation & Special Needs, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur. PARTICIPANTS: A total of 79 parents and 23 siblings from 44 families of children with CI participated in this study. MAIN OUTCOME MEASURES: The mean score for each of the sub-domain and the overall QoL for both subject groups were computed. The answers for the open-ended questions were listed and organized into themes. RESULTS: There were significant correlations between the overall QoL score and each of the test domains for the parents' group (p < 0.01). For the siblings' group, only the interaction and support domains were significant. Interaction was the main sub-domain affecting the parents' QoL but for siblings, this could not be determined. A total of 60% of the pooled comments were classified as ‘concerns’. As for the suggestions, 38.7% requested some form of support, mainly financial (41.7%). CONCLUSIONS: Families with hearing impaired children with CI have numerous concerns that need to be addressed, even though, on average, they were satisfied with their overall QoL.